The Hebb Synapse Before Hebb: Theories of Synaptic Function in Learning and Memory Before Hebb (1949), With a Discussion of the Long-Lost Synaptic Theory of William McDougall - Brown, Richard E.; Bligh, Thaddeus W. B.; Garden, Jessica F. (Frontiers in Behavioral Neuroscience, 2021)
Since the work of Semon was rediscovered by Schacter in 1978, there has been a renewed interest is searching for the “engram” as the locus of memory in the brain and Hebb’s cell assembly has been equated with Semon’s engram. There have been many theories of memory involving some concept of synaptic change, culminating in the “Hebb Synapse” theory in 1949. However, Hebb said that the idea that any two cells or systems of cells that are repeatedly active at the same time will tend to become “associated,” was not his idea, but an old one. In this manuscript we give an overview of some of the theories of the neural basis of learning and memory before Hebb and describe the synaptic theory of William McDougall, which appears to have been an idea ahead of its time; so far ahead of its time that it was completely ignored by his contemporaries. We conclude by examining some critiques of McDougall’s theory of inhibition and with a short discussion on the fate of neuroscientists whose ideas were neglected when first presented but were accepted as important many decades later.